Threat Modeling: Designing for Security - Adam Shostack (Indianapolis, IN Wiley, 2014)
The book is chock-full of specific and actionable advice, without being tied to specific software, operating systems or languages. For security professionals, the book provides the easiest way to adopt a structured approach to threat modeling. This approach is being promoted by Microsoft, and the book will provide the easiest way to understand the changing threats and threat landscape. The book is up-to-date and covers all of the methods of threat modeling. For software developers, threat modeling is big and scary and hard to get your arms around. But as more software is delivered on the Internet, or operates on Internet connected computers, as attackers move after money, developers can no longer afford to view software security as an afterthought or as a matter of features. This book provides a jargon-free and accessible introduction to this important skill. For systems managers with security responsibilities, this book provides tools and a framework for structured thinking about what goes wrong. By threat modeling, they can break away from a technology centered way of threat modeling and instead focus on threats and effective operational countermeasures.The book begings with learning how to threat model, threat modeling approaches such as asset centric, attacker centric and sofware centric, then on to specifics such as threats to cryptosystems and finally moves on to more advanced areas with many examples to follow and emulate such as 3-tier web app, phone app, validation and cargo cutting.
Keywords: Nonfiction; Science; Programming; Computer Science